2009
DOI: 10.1097/inf.0b013e3181958769
|View full text |Cite
|
Sign up to set email alerts
|

Pathogens Associated With Sepsis in Newborns and Young Infants in Developing Countries

Abstract: Limited information is available on etiology of serious bacterial infections in community settings. Hospital-based studies suggest that most infections in the first week of life are due to Gram-negative pathogens, and many may be environmentally rather than maternally-acquired, owing to unhygienic delivery practices. Such practices may also explain the predominance of Gram-negative infections among home-born infants, although data from home settings are limited. These findings have implications for developing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
258
2
14

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(288 citation statements)
references
References 54 publications
14
258
2
14
Order By: Relevance
“…In addition, given that sepsis in SSA is caused by several bacterial species, any preventive measure should cover a wider spectrum of bacteria. 2,3,5 Maternal infections, which include puerperal sepsis, mastitis, and other infections occurring during the postpartum period, remain an important cause of maternal morbidity and mortality, particularly in developing countries. 6 Although reliable population-based estimates of maternal sepsis in SSA are not available, a recent World Health Organization (WHO) systematic review showed that >1 out of 9 maternal deaths reported worldwide are due to puerperal sepsis.…”
Section: What This Study Addsmentioning
confidence: 99%
“…In addition, given that sepsis in SSA is caused by several bacterial species, any preventive measure should cover a wider spectrum of bacteria. 2,3,5 Maternal infections, which include puerperal sepsis, mastitis, and other infections occurring during the postpartum period, remain an important cause of maternal morbidity and mortality, particularly in developing countries. 6 Although reliable population-based estimates of maternal sepsis in SSA are not available, a recent World Health Organization (WHO) systematic review showed that >1 out of 9 maternal deaths reported worldwide are due to puerperal sepsis.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Limited epidemiological data from developing countries show higher rates of certain pathogens, such as nontyphoidal Salmonella (27). We hypothesize that the epidemiologic similarities suggested in our study may reflect limitations in laboratory resources, with the responsible infectious agent in many cases either assumed or unknown.…”
Section: Discussionmentioning
confidence: 64%
“…In developed countries, it has been reported that 30 to 40% of meningitis cases are Gram-negative, and that E. coli is the most frequent bacterium 1,2 . In developing countries, Gram-negative meningitis is more frequent 4,14 . The predominance of Gram-negative bacteria in the present study reflected the bacteriological pattern in the NICU in the late 1990s and early 2000s 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococci predominated among the Gram-positive agents and they are currently the main agents causing late-onset sepsis 4,14 . A multicenter study involving 134 very low birth weight premature infants with confirmed meningitis showed that Gram-positive agents were responsible for 63% of the episodes, with occurrences of coagulase-negative staphylococci in 29% of the cases.…”
Section: Discussionmentioning
confidence: 99%